Tindak Pidana Korupsi Dalam Pandangan Hindu - Yase, I Kadek Kartika (IAHN Tampung Penyang Palangka Raya, 2020)
Corruption is a crime that is likened to a chronic disease, difficult to eliminate. Hindus perceive acts of corruption as violating the Tri Kaya Parisudhaconcept of thinking, saying and doing good. Acts of corruption are also part of the Panca Ma, namely five actions that can keep people from the path of dharma. Panca Maconsists of Madat(addict), Memunyah(drunk), Memotoh(gambling), Madon(playing woman), and Mamaling(stealing/corruption). In addition, corruption also violates the concept of Catur Purusa Artha, namely the four goals of human life consisting of dharma/truth, artha/treasure, kama/desire and moksa/Brahmannature. Where corruption has violated the dharmato get wealth. The act of corruption is caused by the fact that it has entered Kaliera, one of which is corruption everywhere. Another cause is the inability of humans to control Sad Ripu, namely six enemies within themselves, which consist of Kama(desire), Lobha(greedy), Krodha(angry), Moha(confused), Mada(intoxicated), and Matsarya(spiteful). The impact of acts of corruption such as an unhappy and ordeal life will be felt by the perpetrator, his family and his offspring. Moksaas the ultimate goal of human life certainly will not be achieved. All that is the work of the law of karmaor the law of cause and effect, the size of an action will bear fruit.